Provision of primary care pharmacy operated by hospital pharmacist - Suratchada Chanasopon; Kritsanee Saramunee; Tanupat Rotjanawanitsalee; Natt Jitsanguansuk; Surasak Chaiyasong (AIMS Press, 2023)
A primary care pharmacy (PCP) is operated by hospital pharmacists in Thailand. This study aims to explore the level of PCP provisions operated by hospital pharmacists, to identify health service components that affect PCP operation and to collect opinions from pharmacists regarding factors influencing PCP operation. A postal survey was conducted in northeastern Thailand. A questionnaire included: (1) the PCP checklist (36 items), (2) questions investigating the health service components required for PCP operation (13 items), and (3) queries to pharmacists concerning factors influencing PCP operation (16 items). Questionnaires were mailed to 262 PCP pharmacists. The PCP provision score was calculated with a max score of 36, and reaching at least 28.8 points was deemed as having 'met expectation'. Multivariate logistic regression with a backward approach was used to determine health service components which affected PCP operation. Most respondents were female (72, 60.0%), aged 36.0 years (IQR 31.0-41.0) and PCP work experience of 4.0 years (IQR 2.0-10.0). Overall, the PCP provision score had met expectation (median = 29.00, Q1-Q3 = 26.50-32.00). Tasks that met expectation involved managing the medicine supply, a home visit with a multidisciplinary team and protecting consumer health. Improving medicine dispensary and promotion of self-care and herbal use were below expectation. PCP operation depended on doctor involvement (OR = 5.63 95% CI 1.07-29.49) and public health practitioner involvement (OR = 3.12 95% CI 1.27-7.69). The pharmacist's responsibility, i.e., a good relationship with the community, likely increased PCP provision. The PCP has been widely instituted in Northeast Thailand. Doctors and public health practitioners should get involved regularly. Further research is needed to monitor the outcomes and value of PCPs.